Effect of Etching Solution Concentration on Track Diameter Development in CR-39 Nuclear Track Detector - Mushtaq Abed Dawood Al-Jubbori (Jordan Journal of Physics, 2025)
Extended Abstract: In this work, two empirical relations related to the track diameter development of alpha particle tracks in CR-39 detectors and to the detector bulk etch rate as a function of concentration of etching solution are suggested and tested. The first empirical equation is a further extension of the equation suggested in reference [13] to accommodate the relation of the track diameter to both etching time and concentration effects. The second equation describes the bulk etch rate as a function of concentration of etching solution. The bulk etch rate is determined by the measurement of the removed layer method. In the process of developing these two equations, tracks formed on CR-39 track detector by 3 MeV alpha particles are etched at four NaOH etching solution concentrations of 4, 6, 8, and 10 N. The etching solution temperature is kept constant at 70oC. Digital image processing method for diameter and detector thickness measurements is used. The study of track sensitivity measurements resulted is estimating that the optimum etching solution concentration is 6N at 70oC. . . . Keywords: CR-39 detector, Bulk etch rate, Etching Solution Concentration, Empirical equations.